2020
DOI: 10.1088/1748-605x/ab9bb2
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species-sensitive nanophotosensitizers of aminophenyl boronic acid pinacol ester conjugated chitosan-g-methoxy poly(ethylene glycol) copolymer for photodynamic treatment of cancer

Abstract: The aim of this study is to prepare reactive oxygen species (ROS)-sensitive nanophotosensitizers for targeted delivery of chlorin e6 (Ce6) and photodynamic tumor therapy. For this purpose, thiodipropionic acid (TDPA) was conjugated with phenyl boronic acid pinacol ester (PBAP) (TDPA-PBAP conjugates) and then the TDPA-PBAP conjugates were attached to the chitosan backbone of chitosan-g-methoxy poly(ethylene glycol) (ChitoPEG) copolymer (ChitoPEG-PBAP). Ce6-incorporated ChitoPEG-PBAP nanophotosensitizers have an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Furthermore, CAPE-loaded poly(DL-lactide-co-glycolide) nanoparticles are more effective in the reduction of mutagenicity than the free CAPE itself [40]. We also prepared CAPE-incorporated nanoparticles using HAsPBPE conjugates since HA is a biocompatible and water-soluble biopolymer, and TbEA-PBPE moiety acts as a hydrophobic moiety in polymer backbone [45]. Then, HAsPBPE conjugates may form core-shell type nanoparticles, i.e., HA acts as an outershell of the nanoparticles while TbEA-PBPE is composed of the hydrophobic inner-core of the nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, CAPE-loaded poly(DL-lactide-co-glycolide) nanoparticles are more effective in the reduction of mutagenicity than the free CAPE itself [40]. We also prepared CAPE-incorporated nanoparticles using HAsPBPE conjugates since HA is a biocompatible and water-soluble biopolymer, and TbEA-PBPE moiety acts as a hydrophobic moiety in polymer backbone [45]. Then, HAsPBPE conjugates may form core-shell type nanoparticles, i.e., HA acts as an outershell of the nanoparticles while TbEA-PBPE is composed of the hydrophobic inner-core of the nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, nanoparticles can be modified to be sensitive to physicochemical stimulus such as radiation, pH, ROS, magnetic field, and light [32][33][34][35][36][37]. HAsPBPE nanoparticles can respond to ROS since the PBPE moiety and thiol group in TbEA in the polymer backbone are known to have ROS-sensitivity and these moieties are able to be decomposed in the oxidative stress [45].…”
Section: Discussionmentioning
confidence: 99%
“…Then, abnormalities of the tumor microenvironment endow nanoparticles to be sensitive to tumor. Particularly, nanoparticles having ROS-sensitivity gives an opportunity to target tumor tissue to maximize anticancer drug exposure in the site of higher ROS level [ 44 , 45 ]. Jang et al reported that biodegradable nanofiber mats having diselenide linkages have responsiveness against ROS and then specifically release anticancer drug according to ROS level in aqueous solution [ 45 ].…”
Section: Discussionmentioning
confidence: 99%